2021
DOI: 10.3390/ijms22179134
|View full text |Cite
|
Sign up to set email alerts
|

Prostaglandin E2 Receptor 4 (EP4) Affects Trophoblast Functions via Activating the cAMP-PKA-pCREB Signaling Pathway at the Maternal-Fetal Interface in Unexplained Recurrent Miscarriage

Abstract: Implantation consists of a complex process based on coordinated crosstalk between the endometrium and trophoblast. Furthermore, it is known that the microenvironment of this fetal–maternal interface plays an important role in the development of extravillous trophoblast cells. This is mainly due to the fact that tissues mediate embryonic signaling biologicals, among other molecules, prostaglandins. Prostaglandins influence tissue through several cell processes including differentiation, proliferation, and promo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 54 publications
0
1
0
Order By: Relevance
“…In addition, in nearly 50% of RSA cases, the cause is unknown and these are referred to as unexplained recurrent spontaneous abortions (URSAs) (4). Studies have suggested that most of the URSAs are related to immune and genetic factors (5)(6)(7)(8). The paucity of data related to the mechanisms of URSAs has hindered the development of effective treatments.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, in nearly 50% of RSA cases, the cause is unknown and these are referred to as unexplained recurrent spontaneous abortions (URSAs) (4). Studies have suggested that most of the URSAs are related to immune and genetic factors (5)(6)(7)(8). The paucity of data related to the mechanisms of URSAs has hindered the development of effective treatments.…”
Section: Introductionmentioning
confidence: 99%